The Influence of Leadership and Compensation on Employee Performance at PT. Passokorang Palu Branch - Ari Ardiansah; Andi Indriani Ibrahim; Yoberth Kornelius; Moh Ali Murad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to examine the effect of leadership and compensation on employee performance at PT Passokorang Palu Branch. Using a quantitative approach with a survey method, all 70 employees were selected through total sampling. Data were analyzed using multiple linear regression. Results indicate that both leadership and compensation have a positive and significant effect on employee performance. These findings imply the need for effective leadership and fair compensation systems to enhance motivation and productivity in the workplace. Keywords: Leadership, compensation, employee performance, motivation, productivity, organizational effectiveness